The importance of leadership and management in process safety. Issue 2 (30th January 2013) - King, Charles
<x xml:space="preserve">Abstract</x> Process safety management (PSM) is often presented as technically complex, requiring a large staff of engineers and specialists with an array of tools and techniques that appear to grow in intricacy and sophistication year by year. Large companies are generally well positioned to operate in this arena—they have the resources to afford a staff of professionals and invest in system development, research specific problem areas, and construct elaborate PSM programs. Smaller enterprises can have similar risks, yet seldom have the internal resources and expertise to match the PSM efforts of the majors. The role of management can be over‐simplified to employing the right expertise to take care of process safety. It is proposed that PSM is not, in fact, a technical issue but one of management and leadership. Keeping a plant safe is managerially complex, demanding strong leadership and attention from senior site management. Technically, it is fairly simple and well within the capacity of any organization that deals with hazardous materials. This article examines the key elements of PSM from both the technical and managerial perspectives. The importance of leadership is discussed and its impact on safety examined. A 12‐step guide to safely managing process hazards is outlined, which acknowledges the need for and role of process safety expertise while placing emphasis on the role of senior management: provide the leadership, oversight, and organizational culture for success. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013.